Liquids, Solutions, and Interfaces : From Classical Macroscopic Descriptions to Modern Microscopic Details. - Fawcett, W. Ronald (Johns Hopkins University/Applied Physics Laboratory series in science and engineering., 2004)
Fundamental Constants1. The Thermodynamics of Liquid Solutions2. The Structure of Liquids3. Electrolyte Solutions4. Polar Solvents5. Spectroscopic Studies of Liquid Structure and Solvation6. Non-Equilibrium Phenomena in Liquids and Solutions7. Chemical Reaction Kinetics in Solution8. Liquids and Solutions at Interfaces9. Charge Transfer Equilibria at Interfaces10. The Electrical Double LayerAppendix A. Mathematical BackgroundAppendix B. The Laws of Electricity and MagnetismAppendix C. Numerical Methods of Data AnalysisIndex.